Entrustment Decision Making: Extending Miller's Pyramid. (13th October 2020) - ten Cate, Olle; Carraccio, Carol; Damodaran, Arvin; Gofton, Wade; Hamstra, Stanley J.; Hart, Danielle E.; Richardson, Denyse; Ross, Shelley; Schultz, Karen; Warm, Eric J.; Whelan, Alison J.; Schumacher, Daniel J.
Abstract : The iconic Miller's pyramid, proposed in 1989, characterizes 4 levels of assessment in medical education ("knows, " "knows how, " "shows how, " "does"). The frame work has created a worldwide awareness of the need to have different assessment approaches for different expected outcomes of education and training. At the time, Miller stressed the innovative use of simulation techniques, geared at the third level ("shows how"); however, the "does" level, assessment in the workplace, remained a largely uncharted area. In the 30 years since Miller's conference address and seminal paper, much attention has been devoted to procedures and instrument development for workplace-based assessment. With the rise of competency-based medical education (CBME), the need for approaches to determine the competence of learners in the clinical workplace has intensified. The proposal to use entrustable professional activities as a framework of assessment and the related entrustment decision making for clinical responsibilities at designated levels of supervision of learners (e.g., direct, indirect, and no supervision) has become a recent critical innovation of CBME at the "does" level. Analysis of the entrustment concept reveals that trust in a learner to work without assistance or supervision encompasses more than the observation of "doing" in practice (the "does" level). It implies the readiness of educators to accept the inherent risks involved in health care tasks and the judgment that the learner has enough experience to act appropriately when facing unexpected challenges. Earning this qualification requires qualities beyond observed proficiency, which led the authors to propose adding the level "trusted" to the apex of Miller's pyramid.